Evaluation of diagnostic strategies for bladder cancer using computed tomography (CT) urography, flexible cystoscopy and voided urine cytology: Results for 778 patients from a hospital haematuria clinic - Blick, C; Nazir, SA; Mallett, S; Turney, B; Onwu, N; Roberts, I; Crew, J; Cowan, N (2012)
OBJECTIVES: • To evaluate and compare the diagnostic accuracy of computed tomography (CT) urography with flexible cystoscopy and voided urine cytology for diagnosing bladder cancer. • To evaluate diagnostic strategies using CT urography as: (i) an additional test or (ii) a replacement test or (iii) a triage test for diagnosing bladder cancer in patients referred to a hospital haematuria rapid diagnosis clinic. PATIENTS AND METHODS: • The clinical cohort consisted of a consecutive series of 778 patients referred to a hospital haematuria rapid diagnosis clinic from 1 March 2004 to 17 December 2007. Criteria for referral were at least one episode of macroscopic haematuria, age > 40 years and urinary tract infection excluded. Of the 778 patients, there were 747 with technically adequate CT urography and flexible cystoscopy examinations for analysis. • On the same day, patients underwent examination by a clinical nurse specialist followed by voided urine cytology, CT urography and flexible cystoscopy. Voided urine cytology was scored using a 5-point system. CT urography was reported immediately by a uroradiologist and flexible cystoscopy performed by a urologist. Both examinations were scored using a 3-point system: 1, normal; 2, equivocal; and 3, positive for bladder cancer. • The reference standard consisted of review of the hospital imaging and histopathology databases in December 2009 for all patients and reports from the medical notes for those referred for rigid cystoscopy. Follow-up was for 21-66 months. RESULTS: • The prevalence of bladder cancer in the clinical cohort was 20% (156/778). For the diagnostic strategy using CT urography as an additional test for diagnosing bladder cancer, when scores of 1 were classified as negative and scores of 2 and 3 as positive, sensitivity was 1.0 (95% confidence interval [CI] 0.98-1.00), specificity was 0.94 (95% CI 0.91-0.95), the positive predictive value (PPV) was 0.80 (95% CI 0.73-0.85) and the negative predictive value (NPV) was 1.0 (95% CI 0.99-1.00). • For the diagnostic strategy using CT urography as a replacement test for flexible cystoscopy for diagnosing bladder cancer, when scores of 1 were classified as negative and scores of 2 and 3 as positive, sensitivity was 0.95 (95% CI 0.90-0.97), specificity was 0.83 (95% CI 0.80-0.86), the PPV was 0.58 (95% CI 0.52-0.64), and the NPV was 0.98 (95% CI 0.97-0.99). Similarly using flexible cystoscopy for diagnosing bladder cancer, if scores of 1 were classified as negative and scores of 2 and 3 as positive, sensitivity was 0.98 (95% CI 0.94-0.99), specificity was 0.94 (95% CI 0.92-0.96), the PPV was 0.80 (95% CI 0.73-0.85) and the NPV was 0.99 (95% CI 0.99-1.0). • For the diagnostic strategy using CT urography and flexible cystoscopy as a triage test for rigid cystoscopy and follow-up (option 1), patients with a positive CT urography score are referred directly for rigid cystoscopy, and patients with an equivocal or normal score were referred for flexible cystoscopy. Sensitivity was 1.0 (95% CI 0.98-1.0), specificity was 0.94 (95% CI 0.91-0.95), the PPV was 0.80 (95% CI 0.73-0.85), and the NPV was 1.0 (95% CI 0.99-1.0). • For the diagnostic strategy using CT urography and flexible cystoscopy as a triage test for rigid cystoscopy and follow-up (option 2), patients with a positive CT urography score are referred directly for rigid cystoscopy, patients with an equivocal score are referred for flexible cystoscopy and patients with a normal score undergo clinical follow-up. Sensitivity was 0.95 (95% CI 0.90-0.97), specificity was 0.98 (95% CI 0.97-0.99), the PPV was 0.93 (95% CI 0.87-0.96), and the NPV was 0.99 (95% CI 0.97-0.99). • For voided urine cytology, if scores of 0-3 were classified as negative and 4-5 as positive for bladder cancer, sensitivity was 0.38 (95% CI 0.31-0.45), specificity was 0.98 (95% CI 0.97-0.99), the PPV was 0.82 (95% CI 0.72-0.88) and the NPV was 0.84 (95% CI 0.81-0.87). CONCLUSIONS: • There is a clear advantage for the diagnostic strategy using CT urography and flexible cystoscopy as a triage test for rigid cystoscopy and follow-up (option 1), in which patients with a positive CT urography score for bladder cancer are directly referred for rigid cystoscopy, but all other patients undergo flexible cystoscopy. • Diagnostic accuracy is the same as for the additional test strategy with the advantage of a 17% reduction of the number of flexible cystoscopies performed. • The sensitivity of voided urine cytology is too low to justify its continuing use in a hospital haematuria rapid diagnosis clinic using CT urography and flexible cystoscopy. © 2011 BJU International.